Review: Placental transport and metabolism of energy substrates in maternal obesity and diabetes. (June 2017) - Gallo, L.A.; Barrett, H.L.; Dekker Nitert, M.
Abstract: Maternal obesity is growing in prevalence and is associated with increased morbidity and mortality for both mother and child. Women who are obese during pregnancy have a greater risk of metabolic complications such as gestational diabetes mellitus (GDM) as well as type 2 diabetes after pregnancy. Children of obese and/or GDM mothers have an increased susceptibility to congenital abnormalities and a range of cardio-metabolic disorders. The placenta is at the interface of the maternal and fetal environments and, its function per se, plays a major role in dictating the impact of maternal health on fetal development. Here, we review the literature on how placental function is affected in pregnancies complicated by obesity, and pre-gestational and gestational diabetes. The focus is on the availability of three key substrates in these conditions: glucose, lipids, and amino acids, and their impact on placental metabolic activity. Maternal obesity and diabetes are not always associated with fetal compromise and the adaptation of the placenta may partially determine the outcome. Understanding the differences in metabolic adaptation may open avenues for therapeutic development.